Microfluidics-based on-a-chip systems for isolating and analysing extracellular vesicles. Issue 1 (1st January 2018) - Guo, Shang-Chun; Tao, Shi-Cong; Dawn, Helen
ABSTRACT: Extracellular vesicles (EVs), which can be found in almost all body fluids, consist of a lipid bilayer enclosing proteins and nucleic acids from their cells of origin. EVs can transport their cargo to target cells and have therefore emerged as key players in intercellular communication. Their potential as either diagnostic and prognostic biomarkers or therapeutic drug delivery systems (DDSs) has generated considerable interest in recent years. However, conventional methods used to study EVs still have significant limitations including the time-consuming and low throughput techniques required, while at the same time the demand for better research tools is getting stronger and stronger. In the past few years, microfluidics-based technologies have gradually emerged and have come to play an essential role in the isolation, detection and analysis of EVs. Such technologies have several advantages, including low cost, low sample volumes, high throughput and precision. This review summarizes recent advances in microfluidics-based technologies, compares conventional and microfluidics-based technologies, and includes a brief survey of recent progress towards integrated "on-a-chip" systems. In addition, this review also discusses the potential clinical applications of "on-a-chip" systems, including both "liquid biopsies" for personalized medicine and DDS devices for precision medicine, and then anticipates the possible future participation of cloud-based portable disease diagnosis and monitoring systems, possibly with the participation of artificial intelligence (AI).